Emergency General Surgery: evolution of a subspecialty by stealth. Issue 1 (December 2016) - Pearce, L.; Smith, S.; Parkin, E.; Hall, C.; Kennedy, J.; Macdonald, A.
Abstract Background Emergency surgical patients account for around half of all NHS surgical workload and 80 % of surgical deaths. Few trainees opt to CCT in General Surgery, and there is no recognised subspecialty training program in Emergency General Surgery (EGS). Despite this lack of training and relevant assessment by examination, there appears to be an increasing number of EGS posts advertised. This study aims to provide information about potential future employment opportunities for surgical trainees. Methods All consultant surgeon posts, advertised in the British Medical Journal between January 2009 and December 2014 were included. Data collected included specialty, region and institute of advertised post. For the purposes of statistical analysis, data was divided into two separate year bands: 2009–2011 and 2012–2014. Statistical analysis was by Chi-squared test;p <0.01 was considered statistically significant. An online tool was also used to determine experience and attitudes towards EGS amongst Consultant members of the ASGBI and all UK trainees in national training number (NTN) posts. Results Over the six-year study period, there were 1240 consultant job adverts in a general surgical specialty. Nine hundred and 75 were substantive posts; the region with the most jobs was London and the South East (n = 278). There were 55 jobs advertised in EGS, either with (20) or without (35) another subspecialty. The number of EGS adverts increased significantly in 2012–14 compared to 2009–11 (p = 0.008). 229 (28 %) Consultants and 309 (22 %) trainees responded to the survey. 16 % of consultants work in NHS institutions with Emergency General Surgeons. Only 21 % of trainees believe EGS will be delivered by EGS consultants in the future whilst 8.2 % of trainees stated EGS as their career plan. Less than half of all UK consultant surgeons see EGS as a subspecialty. Conclusions This data demonstrates increasing societal need for EGS consultants over the last six years and the emergence of Emergency Surgery as a new subspecialty. In order to meet the EGS needs of the NHS, general surgical training and the examination system need to be revised.